2017
DOI: 10.1002/pa.1686
|View full text |Cite
|
Sign up to set email alerts
|

Performance health administration and the return of the French second empire

Abstract: In the French health care system, cost‐containment strategies have become the new priority. Novel instrumental values (e.g., benchmarking, incentivization or premiums, and Diagnostic‐Related Groups) and reforms of the hospital governance via the 2009 HPST Act served an austerity agenda at the expense of more patient‐centered approaches (e.g., patient choice and case management). Effecting actual changes proved more difficult than collecting data on the health system. Decision‐making powers are increasingly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Studies have reported that low back pain is the most common MSD in adults and about 60-80% of all individuals will experience the condition at some stage in their life (Waddell & Burton, 2001). Researchers have found that the neck, knees and ankles/feet as the most common body sites of WMSDs among health care practitioners (Devereux, Vlachonikolis, & Buckle, 2002;Smith, Choi, Myung, Kim, & Yamagata, 2003). Our finding on the high prevalence of work-related back, ankle, knee and neck pain among the general surgeons is consistent with the pattern reported in literature (Smith et al, 2006;Szeto et al, 2009).Since very negligible studies were carried out on doctors practicing in Indian hospitals, so no Indian data was available for comparison.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported that low back pain is the most common MSD in adults and about 60-80% of all individuals will experience the condition at some stage in their life (Waddell & Burton, 2001). Researchers have found that the neck, knees and ankles/feet as the most common body sites of WMSDs among health care practitioners (Devereux, Vlachonikolis, & Buckle, 2002;Smith, Choi, Myung, Kim, & Yamagata, 2003). Our finding on the high prevalence of work-related back, ankle, knee and neck pain among the general surgeons is consistent with the pattern reported in literature (Smith et al, 2006;Szeto et al, 2009).Since very negligible studies were carried out on doctors practicing in Indian hospitals, so no Indian data was available for comparison.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…However, consolidated research data in the Indian context seems to be lacking. The results can provide information about the size of the problem and the findings can be used to design health welfare policies for healthcare professionals, develop administrative reforms, intervention strategies for this group and possibly other specialties as well, thereby ensuring a higher quality of life (QoL) and making the work environment safer, healthier without compromising the productivity and profit (Simonet, 2017; Simonet, 2018). The study was undertaken with the following aims: (a) to study the incidences of WMSDs experienced by healthcare workers working in hospitals of India by Nordic Musculoskeletal Questionnaire (NMQ), (b) to quantify the psychosocial stress experienced by nurses through Organizational Role Stress Scale (ORS‐Scale) and Modified Nursing Stress Scale (MNSS), (c) to quantify the psychosocial factors and their possible association with WMSDs in doctors by Re‐modified Work‐style instrument, (d) to evaluate the intensity of pain pre and postexposure of work in doctors by Visual Analogue Scale (VAS), (e) to ascertain the QoL among nurses by Quality of Life Questionnaire (WHOQOL‐BREF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation